Comparative Evolution of Duplicated Ddx3 Genes in Teleosts: Insights from Japanese Flounder, Paralichthys olivaceus. Issue 8 (1st August 2015) - Wang, Zhongkai; Liu, Wei; Song, Huayu; Wang, Huizhen; Liu, Jinxiang; Zhao, Haitao; Du, Xinxin; Zhang, Quanqi
Abstract: Following the two rounds of whole-genome duplication that occurred during deuterostome evolution, a third genome duplication event occurred in the stem lineage of ray-finned fishes. This teleost-specific genome duplication is thought to be responsible for the biological diversification of ray-finned fishes. DEAD-box polypeptide 3 (DDX3) belongs to the DEAD-box RNA helicase family. Although their functions in humans have been well studied, limited information is available regarding their function in teleosts. In this study, two teleost Ddx3 genes were first identified in the transcriptome of Japanese flounder ( Paralichthys olivaceus ). We confirmed that the two genes originated from teleost-specific genome duplication through synteny and phylogenetic analysis. Additionally, comparative analysis of genome structure, molecular evolution rate, and expression pattern of the two genes in Japanese flounder revealed evidence of subfunctionalization of the duplicated Ddx3 genes in teleosts. Thus, the results of this study reveal novel insights into the evolution of the teleost Ddx3 genes and constitute important groundwork for further research on this gene family.